Geographic Record of Human Impact Conformance to Different Water Relationships Along a Coastal River (The Łupawa Catchment) - Drwal, Jan; Cieśliński, Roman; Fac-Beneda, Joanna (Quaestiones Geographicae, 2011)
The purpose of this paper is to answer the following two questions: Can one infer the type of human impact found in the northern Pomorze region from the current state of the Łupawa basin? Did regional water relationships determine the type of human impact found in the area? A good place to search for an answer to these two questions is the Łupawa River drainage basin. The entire upper section of the river, upstream from the Bukowina, is characterized by a lack of substantial changes in the hydrographic network, resulting from man's apparent disinterest in the area. The middle section of the river is characterized by human impact in the form of the use of water resources for energy generation purposes (sawmills, gristmills, power plants). The lower section of the Łupawa that includes Lake Gardno is characterized by significant changes in water relationships associated with difficult discharge conditions. Finally, the mouth section of the river, given its location, has been adapted as a port facility.